2007
DOI: 10.1523/jneurosci.2916-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Anandamide Regulates Postnatal Development of Long-Term Synaptic Plasticity in the Rat Dorsolateral Striatum

Abstract: Long-term changes in synaptic efficacy produced by high-frequency stimulation (HFS) of glutamatergic afferents to the rat dorsolateral striatum exhibit heterogeneity during early stages of postnatal development. Whereas HFS most often induces striatal long-term potentiation (LTP) in rats postnatal day 12 (P12)-P14, the same stimulation tends to induce long-term depression (LTD) at ages P16 -P34. Previous studies have shown that striatal LTD induction depends on retrograde endocannabinoid signaling and activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 48 publications
5
64
0
Order By: Relevance
“…Because FPL-LTD was induced during blockade of PLC with U73122, our data suggest that the dependence of PLC activation becomes redundant during periods of high postsynaptic [Ca 2ϩ ] i , because endocannabinoid production may be stimulated sufficiently by calcium alone (Chevaleyre et al, 2006). Recent studies have suggested that the endocannabinoid anandamide participates in the induction of striatal LTD (Ade and Lovinger, 2007;Kreitzer and Malenka, 2007). Anandamide synthesis can be stimulated by increased intracellular calcium via molecular steps that do not involve PLC (Di Marzo et al, 1994).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Because FPL-LTD was induced during blockade of PLC with U73122, our data suggest that the dependence of PLC activation becomes redundant during periods of high postsynaptic [Ca 2ϩ ] i , because endocannabinoid production may be stimulated sufficiently by calcium alone (Chevaleyre et al, 2006). Recent studies have suggested that the endocannabinoid anandamide participates in the induction of striatal LTD (Ade and Lovinger, 2007;Kreitzer and Malenka, 2007). Anandamide synthesis can be stimulated by increased intracellular calcium via molecular steps that do not involve PLC (Di Marzo et al, 1994).…”
Section: Discussionmentioning
confidence: 80%
“…The strategic position of Ca v 1.3 thus may be crucial for efficient activation of Ca 2ϩ -dependent modulatory cascades involved in LTD induction (Olson et al, 2005). The 2-arachidonoylglycerol (2-AG) synthetic enzyme diacylglycerol lipase also is located in the perisynaptic region of MSN dendritic spines near mGluR5 (Uchigashima et al, 2007), although it must be noted that the role of 2-AG in LTD is still unclear (Ade and Lovinger, 2007;Kreitzer and Malenka, 2007). Thus Ca v 1.3 may be part of a signaling com- Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…In some experiments, the glutamatergic afferents were stimulated by square-wave 50 s electric pulses delivered by a bipolar stimulating electrode placed within the white matter at the corticostriatal border as in the study by Ade and Lovinger (2007) at a frequency of 0.2 Hz. Action potential firing was recorded from single cells in loose cell-attached configuration.…”
Section: Methodsmentioning
confidence: 99%
“…In the hippocampus (Chevaleyre et al 2006;Hashimotodani et al 1997a;Katona et al 2006;Makara et al 2005), cerebellum (Safo and Regehr 2005;Szabo et al 2006;Yoshida et al 2006), striatum (Uchigashima et al 2007), and prefrontal cortex (Lafourcade et al 2007;Melis et al 2004), 2-AG is the most common EC mediating short-and long-term plasticity. However, AEA is involved in EC-dependent LTD in amygdala and the levels of AEA determine the sign of synaptic plasticity in the striatum (Ade and Lovinger 2007;Azad et al 2004). Given the similarities of the DCN with the cerebellum (Oertel and Young 2004), we focused initially on 2-AG.…”
Section: -Arachidonoylglycerol Mediates Ec Signaling In the Dcnmentioning
confidence: 99%